The reflections of the inclusive student's active participation in out-of-class school activities on social development - Bekir Yıldız (Ömer Gökhan Ulum, 2022)
It is expected that students with special needs participating in inclusive education will be able to meet their educational needs within the formal education system, spend time with their peers, and integrate with the society in an environment where they can display their interests and talents. Inclusion students are required to participate in some school activities outside the classroom as well as in-class practices and activities that enable their development. In this study, a case study, which is one of the qualitative research designs was used. The active participation of a student with special needs in a total of 18 school activities in the 2021-2022 academic year constitutes the implementation process. After the application, the impressions of the school stakeholders about the student participating in the out-of-class school activities were determined by the interview method. Research data were collected with "Image Records", "Observation Checklist" and "Mastering Student Evaluation Form" prepared by the researcher. The records obtained during the activity were analyzed descriptively in the categories of developing relationships and taking responsibility. The views of six participants, who were observers of the student's social development, were analyzed descriptively. The findings obtained from the research showed that active participation in out-of-class school activities contributed significantly to the social development of the inclusive student.